VARIASI WAKTU VERNALISASI DALAM PENINGKATAN PRODUKSI DAN VIABILITAS BIJI BAWANG MERAH - Muji bptp (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2019)
ABSTRACT True Shallot Seed(TSS) is a new agricultural innovation technology as a solution to overcome the problems of shallot production in Indonesia. Many factors influence the successful of TSS production such as climate, availability of pollinator insects, quality of shallot bulbs used and various other technological components in spurring the formation of flowers and true seed yield. Vernalisation is one of the important components in the successful production of TSS. This research aim to observe growth performance and productivity of shallot growing from bulbs and viability of true seed yield based on different vernalisation period. The research consists of two stages, the first phase investigate growth variability and TSS yield by testing 4 treatments with 3 replications. The treatments were: 1) without vernalisation, 2)2 weeks vernalisation period, 3) 4 weeks vernalisation period and 4) 6 weeks vernalisation period.The experiment was conducted in East Lombok - Indonesia from May to November 2016, followed by the second phase from December 2016 to January 2017 by testing the viability of TSS produced from first phase. The results showed that 4 weeks vernalisation period gave the best growth performance as indicated by the fastest flower occurring time, largest flower diameter, and highest number of seed yield. In addition, TSS from 4 weeks vernalisation period showed the highest viability in the field.